Facile synthesis of dual-labeling carbon dots for simultaneous visualization of lipid droplets and lysosomes. (15th January 2023) - Gao, Dong; Zhang, Yusheng; Zhu, Yuda; Xin, Nini; Wei, Dan; Sun, Jing; Fan, Hongsong
Abstract: Single fluorescent probes (SFPs) that enable simultaneous and discriminative visualization of multiple organelles are highly desirable due to their great potential in deciphering spatial distributions and interplays among these organelles. However, carbon dots (CDs)-based SFPs possessing dual-labeling ability are extremely deficient and challenging. Herein, we report the first example of CDs-based lipid droplets (LDs)/lysosomes dual-targeted SFPs, LD-Ly-CDs, through rational design of covering lipophilic alkyl group (CH3 ) and hydrophilic amino residue (-NH2 ) on the surface. LD-Ly-CDs allow to discriminate LDs and lysosomes via the ultrasensitive fluorescence response towards their distinct polarity. With the probe LD-Ly-CDs, the distribution, size morphology and polarity of LDs and lysosomes in different cells are revealed. By the excellent dynamic recognition properties of LD-Ly-CDs, two fast and unpredictable LDs coalescence modes, adjacent LDs fusion and migration-mediated LDs coalescence, are discovered. Moreover, the dynamic imaging also uncovers a new model of LDs and lysosomes dynamic as well as an impressive lipolysis process during starvation model. The remarkable performances of LD-Ly-CDs not only provide a powerful tool to elucidate LDs-lysosomes related interactions, but also shed light on the development of dual-labeling carbon-based fluorescent nanomaterials. Graphical abstract: Rational design of novel carbon dots-based lipid droplet (LD)/lysosome dual-targeted single fluorescent probe with ultrahigh quantum yield up to 85.85% for simultaneous and discriminative visualization of LDs and lysosomes under single excitation source. Image 1 Highlights: Lipid droplets/lysosomes dual-labeling carbon dots (LD-Ly-CDs) were reported. LD-Ly-CDs show ultrahigh sensitivity to polarity and high QY up to 85.85%. The relationship between surface chemistry and dual-targeting ability is revealed. LD-Ly-CDs allow simultaneous and discriminative imaging of lipid droplets and lysosomes. Dynamic interactions between lipid droplets and lysosomes are monitored by LD-Ly-CDs.